Implementasi Routing Terdistribusi pada Mobile AD HOC Networks (MANETS) untuk Sistem Komunikasi Taktis - Tassia, Shelvi Eka (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Military communication, known tactical communications. Tactical communications support military operations is the region that does not have a fixed network infrastructure. Appropriate technology to support performance of tactical communication is Mobile Ad Hoc Networks (MANETs). Node in MANET has dynamic characteristics that will significantly influence the composition of the network topology. In tactical Mobile Ad Hoc Networks, problems that occur is the vulnerability to changes in the network topology due to node mobility. The solution face this problems is the routing protocol is suitable for use in MANET. In this study, used an approach in terms of distributed routing mechanism. In distributed routing mechanism, each node informed about the status of other nodes in the same network, and storage the information is within their local database respectively. TORA and AODV can support this mechanism, so in this study two of routing protocols will be compared in terms of dynamic adaptability, routing overhead, end-to-end delay and throughput. From this research, AODV produce better performance than TORA. For the speed of 10 m/s, the measurement of end-to-end delay is the smallest 1245.376 ms, increase in throughput of 74.363 % and the adaptability of 30.179. But the routing overhead generated greater, amounting 1359.